Intra-industry trade in the automobile sector: the Portugese experience - Leitão, Nuno Carlos (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
This study examines the determinants of intra-industry trade (IIT), horizontal IIT (HIIT) and vertical IIT (VIIT) in the automobile industry in Portugal. The trade in this sector between Portugal and the European Union (EU-27) was examined, between 1995 and 2008. These results indicate that intra-industry trade occurs more frequently among countries that are similar in terms of factor endowments. The findings support the theory that, in general, there is no positive statistical association between HIIT and Heckscher-Ohlin variables. We also introduce the economic dimension, and common border; these proxies confirm the positive effects in bilateral trade. Our results also confirm the hypothesis that trade increases if transportation costs decrease
Argumenta Oeconomica, 2011, Nr 2 (27), s. 125-136
Keywords: horizontal intra-industry trade; vertical intra-industry trade; Portugal; automobile industry